PERANCANGAN ALAT PENGUKURAN SUHU DAN KADAR OKSIGEN DALAM TUBUH BERBASIS MIKROKONTROLER - Nugroho, Fifto; Ulan Bani, Alexius; Esperito Epifanius Velazques, Emmanuel (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2022)
The development of modern technology makes it possible to make a more advanced tool. The health sector as one of the important components of life also does not escape the support of technology. One of the implementations is the design and manufacture of a system for measuring temperature and oxygen levels in the body. Measurements are made using the fingers to detect oxygen levels and the hands to detect the temperature without injuring the body. This measuring instrument uses the MAX30100 sensor, MLX90614, Arduino Uno, 16x2 LCD with I2C and Buzzer. This tool is able to measure temperature and oxygen levels with a buzzer as a sound indicator if conditions are not appropriate / abnormal